Analisis Penerapan Konservatisme Akuntansi dalam Perspektif Positive Accounting Theory Pada Bank Umum Syariah di Indonesia - Annisa Helfie Syafila; Reni Oktavia (CV. Ulil Albab Corp, 2023)
The objective of this research is to examine the implementation of accounting conservatism in the context of positive accounting theory, which includes the bonus plan, debt covenant, and political cost hypothesis. The study focused on 45 Islamic Bank Companies listed on Financial Services Authority (OJK) between 2017 and 2021, and the sample was chosen using purposive sampling based on specific criteria. The multiple regression technique was employed for analysis. The results indicate leverage and firm size have a positive effect on accounting conservatism, while capital intensity has a negative effect on accounting conservatism. Public and managerial ownership do not have an impact on accounting conservatism. Therefore, the study concludes that accounting conservatism is affected by leverage, firm size, and capital intensity.